Monitoring of Energy Efficiency of District Heating System Facilities: Methodology for Determining the Energy Baseline - Davydenko L.V.; Davydenko N.V.; Davydenko V.A.; Sprake D. (Problems of the Regional Energetics, 2022)
Determining the energy consumption level is one of the stages of energy efficiency monitoring facilities. The aim of the article is to adapt the energy baseline to the operating conditions of the facility in accordance with the ISO 50000 Standards requirements. The methodology for deter-mining the energy baseline was proposed to achieve the goal. The three-stage procedure for forming a set of relevant variables of the energy baseline, which allows taking into account the significance of variables, the possibility of their measurement, controllability and control, and the procedure for constructing a multifactorial model of the optimal structure for determining the energy baseline are the main scientific results. This methodology was applied to a boiler house of a district heating system. Relevant variables were formed using a three-stage selection of fac-tors that influence the gas consumption efficiency of the boiler house. Combinatorial algorithm of the group method of data handling was used for gas consumption simulation. The search for models of optimal complexity was performed in six classes of basic functions. The selection of better structures of the mathematical model was realized based on the criteria for its appropriate-ness (regularity, unbiasedness criterion, Schwartz, determination coefficient) and accuracy of the forecast using the morphological criterion. As a result, a multifactor mathematical model of optimal structure was obtained. The percent forecasting error did not exceed 1%. The signifi-cance of the results lies in the fact that the proposed methodology can be applied to any facility.